Analysis Study of Goat Livestock Business in Ketty Letpey Village, Southwest Maluku Regency - Welerubun, Inggrid (Sahabat Publikasi, 2024)
The objective of this research is to find out about profits, incomes, and feasibility of goats in Ketty Letppy village, Lakor sub-district in Southwest Maluku regency. The research was conducted from October until November in 2024. The location and 30 respondents are the which were taken by the purposive sampling method. The analysis method consists of income analysis and feasibility analysis. This research showed that the income of respondents was around Rp. 8.005.000, and feasibility analysis (R/C) was around 1.03. The research can beconcluded that the goat farm in Ketty Letppy village, Lakor sub-district in Southwest Maluku regency is feasible to conducting.